Empowering Communities: Harnessing Technology for HIV Literacy and Triple Zero Goals - Ronald Pratama Adiwinoto; Jennifer Wijaya; Alicia Stevina Martono; Fernita Naomi Putri; Vincentia Prasasti; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: The COVID-19 pandemic provides a unique opportunity to reinvigorate efforts to achieve the Triple Zero HIV goal by 2030-zero new cases, zero deaths from AIDS, and zero stigma. This scoping review explores technology, including social media and big data, in increasing HIV literacy and community engagement. It is crucial to prioritize the Triple Zero HIV targets, which involve the eradication of new HIV infections, AIDS-related deaths, and the stigma associated with HIV, amidst the COVID-19 epidemic. This study aimed to rigorously investigate and identify new technology-driven therapeutics to eliminate HIV, AIDS-related fatalities, and social discrimination by 2030. Subjects and Method: A systematic review was conducted by searching articles from PubMed and ResearchGate is an article published from 2015 to present. The keywords were “HIV education technology” and “community engagement.” Articles covering technology-based HIV literacy and community engagement were selected, and other databases were searched extensively for this scoping review. The search included